Adjusting (AlNi)/(FeCr) ratio to tailor microstructure and properties of A2-B2 dual-phase (AlNi)x(FeCr)100-x medium-entropy alloys - Guijiang Diao; Mingyu Wu; Anqiang He; Zhen Xu; Dhruv Bajaj; Daolun Chen; Ranran Fang; Anatoliy Vorobyev; Q.Y. Li; Dongyang Li (Journal of Materials Research and Technology)
Metallic materials composed of alternating soft and hard phases can be tailored for desirable strength-ductility combinations. In this work, (AlNi)x(FeCr)100-x (x = 40, 50 and 60) A2-B2 dual-phase medium-entropy alloys (MEAs) fabricated using an arc-melting furnace were studied. Fractions and morphologies of (Fe, Cr)-rich A2 and (Al, Ni)-rich B2 phases in the alloys were modified by simply adjusting the ratio of (AlNi) to (FeCr), based on phase diagrams calculated using Thermo-Calc software. The (AlNi)x(FeCr)100-x alloys showed different microstructural features, including interdendritic regions with irregular A2-B2 lamellae (in all three alloys), and dendrite cores with different morphologies such as A2 matrix embedded with B2 particles (x = 40), A2-B2 weave-like structure (x = 50), and B2 matrix embedded with A2 nanoparticles (x = 60). Based on micro-indentation tests, all the core zones showed higher hardness than interdendritic regions, benefiting from their weave-like or particle-dispersed microstructure. Compressive tests and EBSD analyses indicated that the presence of the core zone having a structure of B2 matrix embedded with A2 nanoparticles was particularly effective for enhancing the strain-hardening capacity and wear resistance. This study demonstrates a simple way, via directly adjusting the fraction ratio of (AlNi) to (FeCr), to control the heterogeneous structure of this MEA system for desirable properties, which can be extended to other A2-B2 dual-phase multi-principal element alloy systems.